Chronic Kidney Disease Increases Atrial Fibrillation Inducibility: Involvement of Inflammation, Atrial Fibrosis, and Connexins - Qiu, Huiliang; Ji, Chunlan; Liu, Wei; Wu, Yuchi; Lu, Zhaoyu; Lin, Qizhan; Xue, Zheng; Liu, Xusheng; Wu, Huanlin; Jiang, Wei; Zou, Chuan (Frontiers in Physiology, 2018)
Chronic kidney disease (CKD) causes atrial structural remodeling and subsequently increases the incidence of atrial fibrillation (AF). Atrial connexins and inflammatory response may be involved in this remodeling process. In this study, nephrectomy was operated to produce the CKD rat model. Three months post-nephrectomy, cardiac structure, function and AF vulnerability were quantified using echocardiography and electrophysiology methods. Left atrial tissue was tested for quantification of fibrosis and inflammation, and for distribution and expression of connexin (Cx) 40 and Cx43. Echocardiography showed that CKD resulted in left atrial enlargement and left ventricular hypertrophy but without functional changes. CKD caused significant increase in AF inducible rate (91.11% in CKD group versus 6.67% in sham group, P ＜ 0.001) and AF duration (107[0 to 770] seconds in CKD versus 0[0 to 70] seconds in sham, P ＜ 0.001) with prolonged P-wave duration. CKD induced severe interstitial fibrosis, activated the transforming growth factor-β1/Smad2/3 pathway with a massive extracellular matrix deposition of collagen type I and α-smooth muscle actin, and matured the NLR (nucleotide-binding domain leucine-rich repeat-containing receptor) pyrin domain-containing protein 3 (NLRP3) inflammasome with inflammatory cascade response. CKD resulted in an increase in nonphosphorylated-Cx43, decreases in Cx40 and phosphorylated-Cx43, and lateralized distribution of Cx40 and Cx43 proteins with upregulations of Rac-1, connective tissue growth factor and N-cadherin. These findings implicate transforming growth factor-β1/Smad2/3, NLRP3 inflammasome and connexins as potential mediators of increased AF vulnerability in CKD.